Pemberian Hak Guna Usaha di Atas Tanah Hak Komunal Menurut Hukum Pertanahan di Indonesia - Ni Ketut Krismanika; I Putu Gede Seputra; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2020)
The granting of Communal Rights Certificates is done according to Article 18 of the MATR / KBPN regulation No. 10/2016, if it has been decided that by the Governor, the Regent / Mayor in that place there are indeed indigenous peoples, the Officer will report to the Ministry of National Land Agency (hereinafter abbreviated as BPN) so that it is not changed and the registration of Communal Rights for the land contained therein in that area. This study aims to determine the mechanism for granting communal land rights certificates for customary law associations and also to identify tenure rights with communal rights based on agrarian arrangements. This research is a normative legal research with a statutory approach and analysis approach and legal concepts. The results of this study indicate that the Decree of the Minister of Land said that if the results of the research there were indigenous peoples and their land, the inauguration of the indigenous peoples was decided by the ministry of MATR / BPN of the region to determine and register communal rights over their land in the region's BPN. The communal rights being applied for will be issued in the future the communal rights certificate of the customary law community. After the Communal Rights Certificate is issued from the BPN on behalf of the customary community, the use and use can be cooperated with a third party, in this case if there is a party who is applying for a Cultivation Right on the communal right, then the customary law community may negotiate with the applicant, in order to get the same benefits. The conclusion is that the mechanism for granting communal land rights certificates to customary law associations starts from the report of the customary head to the Regent / Mayor and the granting of Building Use Rights on Communal Rights land is allowed as long as Communal Rights as long as the customary community wants to relinquish these rights or exchange with other land.